Corporate Social Responsibility in Small Medium Enterprises: A Scoping Literature Review - Fitriya Andriyani; Sulis Rochayatun (Universitas Jember, 2023)
CSR has become an important issue in business practices in various sectors, including in Small and Medium Enterprises (SMEs). SMEs have a crucial role in the economy, due to their contribution in creating jobs, local economic growth, and poverty reduction. However, SMEs are also faced with various challenges, such as limited resources, market access, as well as limitations in the ability to participate in social initiatives so many considerations are given to implementing CSR practices. Therefore, a literature review on CSR in SMEs is needed to provide an up-to-date overview of CSR research in SMEs. The purpose of this literature is to map the study of the concept of CSR in SMEs. To get relevant articles, data collection techniques are used through the Emerald, Springer, and Google Scholar databases by emphasizing keywords according to the research topic. The results of the study show that the implementation of CSR in SMEs can be an effective strategy in improving the welfare of SMEs and surrounding communities. By strengthening SME CSR and facilitating collaboration with various related parties, SMEs can increase their competitiveness, create a wider positive impact, and contribute to sustainable development. Keywords: Corporate Social Responsibility, Sustainability, SMEs, Scoping Review